Pilot‐scale open‐channel raceways and flat‐panel photobioreactors maintain well‐mixed conditions under a wide range of mixing energy inputs. Issue 4 (23rd January 2020) - Quiroz‐Arita, Carlos; Blaylock, Myra L.; Gharagozloo, Patricia E.; Bark, David; Prasad Dasi, Lakshmi; Bradley, Thomas H.
Abstract: Turbulent mixing in pilot‐scale cultivation systems influences the productivity of photoautotrophic cultures. We studied turbulent mixing by applying particle image velocimetry and acoustic doppler velocimetry to pilot‐scale, flat‐panel photobioreactor, and open‐channel raceway. Mixing energy inputs were varied from 0.1 to 2.1 W·m −3 . The experimental results were used to quantify turbulence and to validate computational fluid dynamics models, from which Lagrangian representations of the fluid motion in these reactors were derived. The results of this investigation demonstrated that differences in mixing energy input do not significantly impact the structure of turbulence and the light/dark cycling frequencies experienced by photoautotrophic cells within the reactors. The experimental and computational results of our research demonstrated that well‐mixed conditions exist in pilot‐scale, flat‐panel photobioreactors and open‐channel raceways, even for relatively low mixing energy inputs. Abstract : Study of the implications of turbulent mixing on the light/dark cycling frequencies experienced by microalgae and cyanobacteria in pilot‐scale flat‐panel photobioreactor and raceway. The research approach consists of (i) experimental fluid mechanics using particle image velocimetry (PIV) and acoustic doppler velocimetry (ADV), (ii) validation of computational fluid dynamics (CFD) models, and (iii) turbulence characterization and particle motion.